System information and notifications of the population: functions and structure - Durnev, Роман Александрович (Chrezvychaynye situatsii: obrazovanie i nauka, 2008)
It is considered new system of informing and notifications of the population, founded on modem information-telecommunication technology. They are determined its role and place in the general system of the provision to safety to vital activity, are installed main functions and structure.